Dandelion Dead. - Fiedler, Chrystle (Fiedler, Chrystle. Natural remedies mystery., 2015)
"Business is blooming at Nature's Way Market & Cafe, and shop owner, holistic doctor, and amateur sleuth, Willow McQuade has never been happier. Her new medicinal herb garden is a hit, so is her new book, she's in love with ex-cop and animal rescuer Jackson Spade, and enjoying teaching seminars about edible plants and natural remedies. But everything changes when Willow's old boyfriend and TV producer, Simon Lewis, winemaker David Farmer, and his wife Ivy, ask her to cater a party at Pure, their new organic vineyard, to kick off North Fork's Uncorked! week and the competition for Wine Lovers magazine's $200,000 prize. Pure's entry, Falling Leaves, is the favorite to win, and the wine flows freely until after Simon's toast when smiles give way to looks of horror. Ivy's twin sister, Amy has been murdered! Turns out, the poison that killed her was actually meant for David. But who wants him dead? A rival vintner? Or someone closer to home? This time the truth may be a bitter vintage to swallow."--Back cover.